Eseng ng Tondo ([s.l.] Viva Films, 1999)
He is a man Manila policeman know for his honesty, fair judgment and incredible marksmanship. His fairness in handling cases, wins him admires, but it also earns him enemies who wants him dead.
VCD
Fernando Poe, Jr., Ina Raymundo
Keywords: Feature films